PENGARUH PERSEPSI SISWA TENTANG KETERAMPILAN MENJELASKAN GURU TERHADAP PEMAHAMAN MATERI AKUNTANSI (Studi Kasus di SMAN 1 Pakusari Semester Genap Tahun Ajaran 2016/2017) - Tri Suci Ulamatullah; Retna Ngesti Sedyati; Bambang Suyadi (Economic Education, University of Jember, 2017)
The purpose of this research is to know the significant influence of students perception about explaining skill of the teachers which consists of 6 indicators those are clear, structured, using example, emphasis, interesting and reversal to the understanding of accounting material in SMAN 1 Pakusari. Determining method of research location used Purposive area in SMAN 1 Pakusari, Jember. Determination of respondents in this study used population method and there were 61 students. Data collection method used consists of some methods: questionnaires, interviews, observations and documents. Data analysis used is inferential analysis that is by simple regression line analysis, regression line variance analysis, F test and effectiveness of regression line / coefficient of determination. The results showed that students' perception on the teachers' explaining skill has a significant effect on the understanding of accounting material that is equal to 79.3%, is mean the perception of students on explaining skill given a positive impact to the understanding of accounting material ,while the remaining 20.7% is influenced by other independent variables that are not examined in this study such as the use of learning media, motivation and students learning interest